Urinary Excretion of Biomolecules Related to Cell Cycle, Proliferation, and Autophagy in Subjects with Type 2 Diabetes and Chronic Kidney Disease - Korbut, Anton I.; Romanov, Vyacheslav V.; Klimontov, Vadim V. (Biomedicines, 2024)
Dysregulation of cell cycle, proliferation, and autophagy plays a pivotal role in diabetic kidney disease. In this study, we assessed urinary excretion of molecular regulators of these processes that mediate their effects via the PI3K/AKT/mTOR pathway in subjects with long-term type 2 diabetes (T2D) and different patterns of chronic kidney disease (CKD). We included 140 patients with T2D and 20 non-diabetic individuals in a cross-sectional study. Urinary PTEN, Beclin-1, sirtuin 1 (SIRT1), Klotho, fibroblast growth factor 21 (FGF21), and connective tissue growth factor (CTGF) were assessed using ELISA. Patients with T2D, when compared to control, demonstrated increased excretion of PTEN, Beclin-1, SIRT1, FGF21, CTGF, and decreased urinary Klotho (all p < 0.05). In the diabetic group, PTEN, FGF21, and CTGF were significantly higher in patients with declined renal function, while Klotho was lower in those with elevated albuminuria. FGF21 and PTEN correlated inversely with the estimated glomerular filtration rate. There was a negative correlation between Klotho and urinary albumin-to-creatinine ratio. In multivariate models, Klotho and PTEN were associated with albuminuric CKD independently. The results provide further support for the role of PTEN, BECN1, FGF21, Klotho, and CTGF in development albuminuric and non-albuminuric CKD in diabetes.